New Insights into the Stratigraphic Setting of Paleozoic to Miocene Deposits Case Studies from the Persian Gulf, Peninsular Malaysia and South-Eastern Pyrenees - Aiello, Gemma (IntechOpen, 2019)
This book contains four chapters dealing with the investigation of facies analysis and paleoecology, chemostratigraphy, and chronostratigraphy referring to paleoecological and facies analysis techniques and methodologies. The chapters pertain in particular to Oligo-Miocene carbonate succession of the Persian Gulf (Asmari Formation), the chemostratigraphy of Paleozoic carbonates of Peninsular Malaysia through the integration of stratigraphic, sedimentologic, and geochemical data, and the chronostratigraphy of a small ice-dammed paleolake in Andorra (Spain), applying fast Fourier transform analysis, resulting in 6th-order stratigraphic cycles, which have outlined the occurrence of system tracts and unconformities controlled by glacio-eustasy. The chapters are separated into four main sections: (1) introduction; (2) facies analysis and paleoecology; (3) chemostratigraphy; and (4) chronostratigraphy. There is one chapter in the first section introducing the stratigraphic setting of Paleozoic to Miocene deposits based on different stratigraphic methodologies, including facies analysis, paleoecology, chemostratigraphy, and chronostratigraphy. In the second section, there is one chapter dealing with the Oligocene-Miocene Asmari Formation, allowing for the recognition of several depositional environments based on sedimentological analysis, distribution of foraminifera, and micropaleontological study. In the third section, there is one chapter aimed at addressing research on the chemostratigraphy of cores, allowing for a significant increase of the stratigraphic knowledge existing on the Kinta Valley (Malaysia), coupled with extensive fieldwork on Paleozoic carbonates. In the fourth section, there is a chapter dealing with the high-resolution chronostratigraphic setting of a paleolake located in Andorra (Spain) and the inference with the MIS2 isotopic stage of Atlantic and Mediterranean regions in the regional geological setting of the southeastern Pyrenees.